Forming a Crisis Resolution Mechanism in International Law - Nagorniak, Mykhailo (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
This article examines modern approaches to assessing the effectiveness of international legal norms, analyzes international law aspects of the use of military force, and defines the criteria of its adminissibility and legitimacy as a means of conflict resolution. It differentiates between inviolability of the state sovereignty and human rights protection in the aspect of military invasion based on humanitarian reasons. This note emphasizes that at the inception of the multipolar international system, the old legal toolkit, which dates back to the Cold War period is incapable of solving problems that arise in the 21th century. The examples provided here demonstrate that not only do the key geopolitical players ignore the current norms of international law and contractual obligations but they also manipulate the law to justify their geopolitical plans. The more resources the countries own the more they are capable of ignoring the norms of international law, thus creating a threat to peace and security in the world. Attention is drawn to the fact that mechanism of solving crises begins to emerge outside the legal field, which leads to an imbalance between the condition of international law and the international legal order. The necessity of reforming the UN, which should be accompanied by the introduction of a number of changes in international law and the revision of the powers and functions of the International Court, is emphasized. Yet any political and legal innovations have to be considered from the perspective of the role of international law as a potential means of protecting the ‘weaker’ states from the ‘more powerful’ ones